Europe and Northeast Asia: Different responses to financial crises - Uwe Wissenbach (Asian Development Bank Institute (ADBI), 2020)
This paper focuses on the critical differences, but also some commonalities, between the EU and three countries in Northeast Asia - the People's Republic of China (PRC), the Republic of Korea, and Japan - in responding to financial crises. The EU's response is naturally multilateral, but the stress test of the sovereign debt crisis showed weaknesses in the integration of economic and monetary policy. The EU strengthened its integration during and after the crisis, oscillating between intergovernmentalism and supranational institutions. This cannot be explained by rational models of stepwise integration, but is eminently political. By contrast, Northeast Asian countries have handled the crisis more successfully in the short term (the jury is still out on the longer-term impact on the massive increase in debt and on slowing growth), but their policy was largely a nationalist one with very limited multilateral coordination, let alone integration, between them. While there are parallels with the objectives of the stabilization measures in the two regions, the design is clearly a major difference that would allow the conclusion to be drawn that the EU is a model of polycentric economic and monetary integration with a number of difficulties revealed in the crisis, while Northeast Asia (and in fact ASEAN+3) is a model of nonintegration with a limited set of grouped bilateral cooperation mechanisms. Neither of the two models is intrinsically superior to the other, but each reveals different political trajectories (or pathways). The global economic impact of the COVID-19 pandemic may allow this analysis to be tested.
Keywords: F55; F33; F; 330; Asian financial crisis; European sovereign debt crisis; global financial crisis; financial safety nets; eurozone